The impact of management control systems on decision-making quality throughout the innovation process. An empirical analysis - Szutowski, Dawid (Wpływ controllingu na jakość decyzji podejmowanych w procesie innowacyjnym. Analiza empiryczna, 2020)
Increasing competition in the present dynamic business environment pressurizes companies to innovate perpetually. The ability to establish and successfully manage a permanent innovation process depends on the quality of decisions made at its consecutive stages. At the same time, management control systems provide managers with the informational basis for decision-making. Thus, the purpose of this paper was to measure the impact of different forms of management control on decision-making quality throughout the innovation process. The analysis was based on a survey conducted amongst the representatives of 64 Polish industrial companies in the third and fourth quarters of 2019 and the first quarter of 2020. Analytical tools included principal component analysis (PCA), used to aggregate data, and multivariate multiple regression models, used to determine the relationships between variables. The findings demonstrate that the relationship between mechanistic and organic forms of management control and decision-making quality may not be analyzed in isolation from the stage of the innovation process. The direction and strength of the relationships between these variables differs at consecutive stages of the innovation process in a statistically significant way
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 182-195